Risk of Tuberculosis among Prisoners: A Case Control Study in Narcotics Prison Class II A Jakarta - Thuffi, Rosalina; Herdayati, Milla; ., Besral (KnE Life Sciences, 2018)
This study aimed to determine the risk factors for tuberculosis in prisons. A case control study conducted at narcotics prison class II.A Jakarta with data collection conducted from December 2013 to February 2014. Seventy-six prisoners who tested positive for tuberculosis and 152 control healthy prisoners were identified. Multivariate logistic regression was applied to determine the risk factors. The results show that significant risk factors for tuberculosis among prisoners were the presence of a person or persons with tuberculosis in the same room, the length of detention, being HIV positive, and no use of antiretrovirals among HIV positive persons. The presence of people with tuberculosis in the same room was the most significant risk factor for acquiring tuberculosis in prison (OR = 13.0, 95% CI 4.4—38.4). Detention for three or more years increased an inmate’s risk of acquiring tuberculosis by 3.7 times (95% CI 1.4–9.5). Those who were HIV positive had a 4.7-times higher risk of tuberculosis (95% CI 1.4–9.5). Those who were HIV positive and did not use antiretrovirals had 5.8 times the risk of contracting tuberculosis compared to controls (95% CI 1.1–31.2). Improvements and modifications, such as isolating those infected with tuberculosis and routine testing for HIV and tuberculosis, can be used in efforts to prevent tuberculosis transmission in prison. Keywords: tuberculosis; prisons; case control